PWE-022 Changing Lifestyle to Reduce Colorectal Cancer in a High Risk Population. (4th June 2013) - Murray, I A; Tarr, G P; John, R; Crowley, A; Kok, J; Mustafa, H; Lee, H-N; Weaver, L; Smith, R; Son, Q; Sii, K M; Cameron, C; et al.
Abstract : Introduction: Both genes and environment are important contributors to colorectal cancer (CRC) risk. Modifying lifestyle has been shown to reduce CRC even in patients with higher genetic risk. Patient anxiety, risk perception and knowledge may affect healthy behaviour change. We examined these and their relation to self-reported lifestyle changes. Methods: 250 patients who had undergone surveillance colonoscopyfor a family history of CRC were randomly selected. A telephone interview was conducted. Demographics, family history, risk factor knowledge, perceptions of lifetime CRC risk, worry due to family history, and self-reported behavioural change due to thoughts about CRC were obtained. General anxiety was assessed using the GAD-7 scale. Ordinal logistics regression was performed to determine significance. Ethics approval was obtained. Results: 148 participants responded (69%). Average age was 55.3 years, 96% were NZ European and over 80% had a lifetime risk of CRC of at least 18% (NZ Guidelines groups 2 & 3). Change in at least one lifestyle measure due to concerns about CRC was reported by 88.5%. Dietary variables and physical activity were more likely to be changed (increased fibre, 63%; increased fruit and vegetables, 54%; reduced red meat, 47%; more physical activity, 45%), with consumption of tobacco, alcohol, and body weight less likely to be altered (25%, 26% and 31% respectively). Adjusted odds ratios for the association of knowledge, anxiety and worry with adoption of healthy behaviours Conclusion: Most patients adopted at least one lifestyle change to reduce their risk. Those with higher anxiety levels, specific worry due to family history, and those who believed they knew more about CRC risk factors were more likely to report healthy lifestyle changes. Overall perceived risk of developing CRC and actual risk due to family history were not associated with behaviour change. Disclosure of Interest: None Declared.